1963
DOI: 10.1039/jr9630002336
|View full text |Cite
|
Sign up to set email alerts
|

432. 2,2′-Bipyrrolic macrocyclic ring systems

Abstract: Metallic derivatives of the 5,5"-bi(dipyrromethene) (I ; R = Br) reacted with hydrochloric acid, ammonia, methylamine, and sodium sulphide to yield the corresponding metallic complexes of the macrocyclic systems (VI; X = 0, NH, NMe, and S). Several reactions of the products are described including the formation of the free base (111) and certain macrocyclic ring openings.ALTHOUGH much is known of the chemistry of porphyrins and azaporphyrins, few modifications of the carbon skeletons of these macrocyclic ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…[8] The porphyrinoid, macrocyclic nature of 2 and 3 is apparent in their optical spectra (see Supporting Information), which contain strong Soret absorption bands near 400 nm, as well as weaker bands between 500 and 650 nm. A comparison of these spectra with literature data [1,9] and with the results of a mass spectrometric study confirms that the products of the oxidative macrocyclizations are indeed the 10-oxacorrole and corrole complexes 2 and 3. In addition, the electron paramagnetic resonance (EPR) spectrum of 2 is consistent with that expected for a porphyrinoid copper(II) system, [10] while 3 is EPR silent.…”
supporting
confidence: 67%
“…[8] The porphyrinoid, macrocyclic nature of 2 and 3 is apparent in their optical spectra (see Supporting Information), which contain strong Soret absorption bands near 400 nm, as well as weaker bands between 500 and 650 nm. A comparison of these spectra with literature data [1,9] and with the results of a mass spectrometric study confirms that the products of the oxidative macrocyclizations are indeed the 10-oxacorrole and corrole complexes 2 and 3. In addition, the electron paramagnetic resonance (EPR) spectrum of 2 is consistent with that expected for a porphyrinoid copper(II) system, [10] while 3 is EPR silent.…”
supporting
confidence: 67%
“…[1] Only little later did the first free-base ligands as well as some nickel(II) and copper(II) chelates become accessible through a simple demetalation/remetalation protocol. [2,3] The tendency of the employed metal ions Ni II , Pd II , and Cu II to bind to dianionic tetrapyrrole ligands in a square-planar fashion, and the UV/Vis-spectroscopic features observed led to the assignment of these compounds to the metalloporphyrin-like structure 1. The first X-ray analysis of a metallobidipyrrin was reported in late 1998 by Dolphin et al [4] Their study of a zinc complex revealed the M 2 L 2 complex 2 and proved that 2,2Ј-bidipyrrin ligands are well suited for adopting different conformations in coordination compounds (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Corrole chemistry, which started in 1964 [2], also led to the ®rst structural characterization of a free-base corrole by Hodgkin and coworkers in 1971 in course of their Vitamin B 12 project [3]. The main research eorts during the years to come were devoted to the synthesis of corroles [4] and to investigation of the coordination chemistry of their metal complexes [5,6].…”
mentioning
confidence: 99%